Quantifying the Benefits of Social Insurance: Unemployment Insurance and Health - Elira Kuka (Institute of Labor Economics (IZA), 2018)
While the Unemployment Insurance (UI) program is one of the largest safety net program in the U.S., research on its benefits is limited. This paper exploits plausibly exogenous changes in state UI laws to empirically estimate whether UI generosity mitigates any of the previously documented negative health effects of job loss. The results show higher UI generosity increases health insurance coverage and utilization, and leads to improved self-reported health. Moreover, these effects are stronger during periods of high unemployment rates. Finally, I find no effects on risky behaviors nor on health conditions.
Keywords: H05; I1; 330; unemployment insurance; health